Source Code Plagiarism in Computer Science Courses: Facts and Impressions - Bazaluk, Bruna; Silva, Flavio S Correa da; Holanda, Maristela; Silva, Dilma Da (Anais do Workshop sobre Educação em Computação (WEI); 2023: Anais do XXXI Workshop sobre Educação em ComputaçãoDO - 10.5753/wei.2023.230066, 2023)
Plagiarism has been a problem in programming courses at different universities around the world. Understanding why students are cheating on their assignments is an important point in this context. This paper analyses the answers of an anonymous questionnaire applied at a Computer Science undergraduate course of a highly reputed Brazilian University concerning the opinion of the students about cheating and plagiarism on programming assignments. When asked if they had already cheated on an assignment, 23.6% of the respondents said they had, and most of them (85.7%) affirmed the reason was the high level of difficulty. Here we discuss some ethic aspects of these situations.